PENGARUH KEPUTUSAN PENGAMBILAN KONSENTRASI MANAJEMEN SUMBER DAYA MANUSIA TERHADAP MINAT MENJADI SEORANG HUMAN RESOURCE DEVELOPMENT di SUATU PERUSAHAAN (Studi Empiris pada Mahasiswa Program Studi Manajemen Universitas Sarjanawiyata Tamansiswa) - Maxmilian Aryanto Dowo Ruing (Bajang Institute, 2022)
The field of Human Resource Management (HRM) is not something that arises suddenly. History has proven that humans have been living in organizations for a long time, although not as intensively as now. This is because HRM itself is all the concepts and techniques needed to handle the personnel, or human resources aspect of a managerial position, such as selection, training, rewarding and appraisal (Garry Dessler in Meldona, 2009: 19). The research method in this study is about the nature of research, operational definitions and indicators of research variables, population, samples and sampling techniques, sources and data collection, data collection place and time, research instrument development, data quality testing and data analysis techniques. Undergraduate Study Program Management, Faculty of Economics, Universitas Sarjanawiyata Tamansiswa is located at Jalan Kusumanegara 121 Yogyakarta. The company started its academic activities in 1979. In 1981 the Faculty of Economics obtained registered status for the Corporate Management Study Program with the Decree of the Minister of Education and Culture No.029/0/1981, under the Coordination of Kopertis Region IV (now Region V) Special Region of Yogyakarta In accordance with the research that has been carried out and the discussion on the effect of the decision making concentration of human resource management on the interest in becoming an HRD in a company, it can be concluded that the decision variable for making the concentration of human resource management (X) has a significant effect on the interest in becoming an HRD ( Y) in a company.